Unmasking Pneumococcal Carriage in a High Human Immunodeficiency Virus (HIV) Prevalence Population in two Community Cohorts in South Africa, 2016–2018: The PHIRST Study. (19th June 2022) - Carrim, Maimuna; Tempia, Stefano; Thindwa, Deus; Martinson, Neil A; Kahn, Kathleen; Flasche, Stefan; Hellferscee, Orienka; Treurnicht, Florette K; McMorrow, Meredith L; Moyes, Jocelyn; Mkhencele, Thulisa; Mathunjwa, Azwifarwi; et al.
Abstract: Background: Longitudinal pneumococcus colonization data in high human immunodeficiency virus (HIV) prevalence settings following pneumococcal conjugate vaccine introduction are limited. Methods: In 327 randomly selected households, 1684 individuals were enrolled and followed-up for 6 to 10 months during 2016 through 2018 from 2 communities. Nasopharyngeal swabs were collected twice weekly and tested for pneumococcus using quantitative lytA real-time polymerase chain reaction. A Markov model was fitted to the data to define the start and end of an episode of colonization. We assessed factors associated with colonization using logistic regression. Results: During the study period, 98% (1655/1684) of participants were colonized with pneumococcus at least once. Younger age (<5 years: adjusted odds ratio [aOR], 14.1; 95% confidence [CI], 1.8–111.3, and 5–24 years: aOR, 4.8, 95% CI, 1.9–11.9, compared with 25–44 years) and HIV infection (aOR, 10.1; 95% CI, 1.3–77.1) were associated with increased odds of colonization. Children aged <5 years had fewer colonization episodes (median, 9) than individuals ≥5 years (median, 18; P < .001) but had a longer episode duration (<5 years: 35.5 days; interquartile range, 17–88) vs. ≥5 years: 5.5 days (4–12). High pneumococcal loads were associated with age (<1 year: aOR 25.4; 95% CI, 7.4–87.6; 1–4 years: aOR 13.5, 95% CI 8.3–22.9; 5–14 years: aOR 3.1, 95% CI, 2.1–4.4 vs. 45–65 year old patients) and HIV infection (aOR 1.7; 95% CI 1.2–2.4). Conclusions: We observed high levels of pneumococcus colonization across all age groups. Children and people with HIV were more likely to be colonized and had higher pneumococcal loads. Carriage duration decreased with age highlighting that children remain important in pneumococcal transmission. Abstract : We observed high levels of pneumococcus colonization in South Africa. Children and people living with human immunodeficiency virus were more likely to be colonized and had higher pneumococcal loads. Carriage duration decreased with age highlighting that children remain important in pneumococcal transmission.